Manipulating practices A critical physiotherapy reader - E Gibson, Barbara; A Nicholls, David; Synne Groven, Karen; Setchell, Jenny (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Manipulating practices is the first ever collection of critical physiotherapy studies and comes at a time of unprecedented change in the profession. Written as a collaboration between 20 authors, many members of the Critical Physiotherapy Network (CPN), the book uncovers the growing body of critical thinking now emerging in physiotherapy. From topics as diverse as 21st century education, ethics, evidence-based practice, touch, and equine therapy; and approaches as varied as disability and performance studies, feminism, logic, narrative theory, new materialism, and phenomenology, the book explores ways of thinking 'otherwise' about physiotherapy. Over 16 chapters written by authors from six different countries, Manipulating practices offers insights from some of physiotherapy's most radical thinkers. The book is also an innovative venture into open source publishing, making it entirely free to download and read. In keeping with the objectives of the CPN, the chapters expose a range of concepts, ideas and practices to critical scrutiny, and reflect the profession's growing interest in critiquing taken-for-granted ways of practicing and thinking. Manipulating practices will be of interest to clinicians, lecturers, policy-makers, researchers and students, and will provide new impetus to help physiotherapists imagine how the profession might grow and develop into the future."